Recreational home owners in the leadership and governance of peripheral recreational communities - Kindel, Grete; Raagmaa, Garri (Hungarian Geographical Bulletin, 2015)
This paper addresses recreational home owners’ role in local leadership and governance, focusing on whether they counteract or reinforce the peripheralisation of remotely located communities. If recreational house owners (RHO) grow in number, they become stronger stakeholders with an increased ability to impact the social and economic life of communities. Possessing high interpretive and network power, they should have fairly good opportunities to contribute to local development. The greatest challenge is to find a balance and create positive synergies between permanent and temporary residents’ interests. Here, leadership quality has a great importance in orchestrating relations and communication between interest groups. Empirically, the paper is based on a comparative case study of Noarootsi and Vormsi, two tiny municipalities located on the Estonian West coast, which is outside the daily commuting area of urban centres. Both case study areas have similar cultural and historical development paths and economic bases. Since they practiced very different leadership models during the last 25 years, we can compare whether and how this impacted governance and overall development. We used media analysis, statistical data and the results of students’ fieldwork as a background; moreover, we conducted 20 in-depth interviews with key informants. The results show the highly important role of RHOs in local governance depending on their personal background and motives. At the same time, the results also indicate the need for skilful local leadership to encourage the participation and equal involvement of all permanent and temporary resident interest groups in decision making.